’Thieves in Our Cultural Heritage’: Crime and Crime Prevention Measures in the Royal Library, Stockholm, 2000-2002 - Lidman, Tomas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
It is almost like the introduction of what promises to be a thrilling crime novel. Unfortunately, the outcome is extremely deplorable. In February 2001 a crudely drawn copy of a map was found on one of the reading room tables at the Royal Library in The Hague. They chose to send it to their colleagues in Copenhagen, who immediately passed it on to us in Stockholm. When we received the faxed map, we noticed that our Library was marked on the map in relation to Döbelnsgatan (one of the smallest streets in Stockholm!) and Åhlens, the large department store located in the centre of the city. The reason why Döbelnsgatan, in particular, had been marked on would come to light later on. This took place on 14 February, and it led to one of the most depressing incidents I have had the misfortune to experience during my time as National Librarian.